Pengaruh Penggunaan Peta Konsep Terhadap Hasil Belajar Siswa Kelas X IPA SMA Negeri 2 Tondano Pada Materi Ikatan Kimia - Adrian Dungir; Sanusi Gugule (Chemistry Department, Universitas Negeri Manado, 2022)
This study was conducted to see the effect of using concept maps on student learning outcomes at SMA Negeri 2 Tondano on chemical bonding material by comparing the average student learning outcomes of the experimental group using concept maps with the control group using conventional methods. The method used in this research is the experimental method in the form of Posttest Only Control Design. The population of this study were all students of class X SMAN 2 Tondano. The sample consisted of a class of 22 students, which were then divided into two groups as the experimental group and the control group, each with 11 students. Data for hypothesis testing is data obtained from the final test. Based on the hypothesis test, the result of significance (2-tailed) was 0.001. Based on the test conditions, if the significance (2-tailed) < 0.05 then Ho is rejected and Ha is accepted. These results indicate that there are significant differences in student learning outcomes from the experimental group and the control group, which means that the use of concept maps has a significant effect on student learning outcomes.